The effects of digital media consumption on perceived well-being - Korolainen, Jesse (2024)
This Master's thesis examines digital media usage patterns, focusing on motivations for using digital media, its effects on daily life, and the factors contributing to addiction. Digital media is an essential part of modern life, providing information, entertainment, and social interaction. Popular social media platforms such as TikTok, Instagram, and YouTube use algorithms to maximise user engagement, raising concerns about compulsive behaviour and its impact on well-being. The study employs a mixed-methods approach, combining qualitative data from diary entries, interviews, and the researcher's own autoethnographic observations. A two-week data collection period was carried out for the study, during which the participants, as well as the researcher, documented their daily experiences related to digital media use while being exposed to stimuli such as removing notifications and apps. The study involved six participants, who discussed their motivations for using digital media and its impact on their perceived well-being. The findings indicate that participants used digital media for stress relief, entertainment, communication, and practical purposes such as navigation for example. Participants recognised the negative effects of digital media use, including sleep disturbances, reduced concentration, and increased anxiety. Excessive social media use led to comparison with others, which in turn caused feelings of inadequacy. The study identifies the factors contributing to digital media addiction as personalised content, short videos, habit formation, and disruptive app notifications, all of which made disengagement difficult and led to addiction-like behaviour patterns. Participants who reduced their digital media use experienced temporary improvements in perceived well-being, sleep quality, and concentration, suggesting the benefits of limiting digital media use. The findings highlight the need to develop healthier digital media practices and ethical platform design that prioritises user well-being.